2013
DOI: 10.1016/j.ejvs.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Brachiobasilic Fistula Formation – Single versus Two Stage Procedure

Abstract: We identified no significant difference of patency between the two methods. This implies that a single stage procedure has benefits, by offering a quicker form of vascular access. Patients who had their fistulae created prior to dialysis had improved patency rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…15 The eight remaining studies that reported on 882 patients met the inclusion criteria and consisted of one randomized controlled trial (RCT) 3 and seven retrospective, observational, cohort studies. 4,5,[16][17][18][19][20] Study baseline characteristics are summarized in Table I. Five of the studies were from the United States, with one each from the United Kingdom, Turkey, and Egypt.…”
Section: Resultsmentioning
confidence: 99%
“…15 The eight remaining studies that reported on 882 patients met the inclusion criteria and consisted of one randomized controlled trial (RCT) 3 and seven retrospective, observational, cohort studies. 4,5,[16][17][18][19][20] Study baseline characteristics are summarized in Table I. Five of the studies were from the United States, with one each from the United Kingdom, Turkey, and Egypt.…”
Section: Resultsmentioning
confidence: 99%
“…Basilic vein diameter, for instance, was the primary consideration in the study by Ozcan et al,4 in which patients with a diameter larger than 3 mm underwent a one-stage procedure. However, vein diameter was not a consideration in the study by Robertson et al,5 in which decisions were dependent on the patient's preference, urgency of fistula, and availability of operating time. 5 This was similarly observed in the study by Ghaffarian et al 6 Interestingly, in the same study, the mean basilic vein diameter was larger in the two-stage arm in comparison to the one-stage arm.…”
Section: Replymentioning
confidence: 99%
“…We noticed that hazard ratio (HR) which is related to time, could be extracted to overcome this bias and would make the result more convincing. For example, in the meta-analysis of mortality, HR could be directly found in the study of Armstrong et al 5 and Bonaca et al 6 In the study of Strobl et al, 3 HR could be extracted and calculated from the Kaplan-Meier curve using Engauge Digitizer. The pooled forest plot (Fig) also suggested that DAPT had superior effect over MAPT in reducing mortality of PAD patients.…”
Section: Replymentioning
confidence: 99%
“…Patency rates of BBF have been shown to be better if the AVF is created when the patient is pre-dialysis. 20 However, given the morbidity associated with the complex, complicated BBF procedure, this calls into question whether preemptive BBF creation in every patient is appropriate. In particular, more than half of the patients who did not use their AVF due to stabilization of renal function were over the age of 70 years.…”
Section: Utilization Of Avfmentioning
confidence: 99%
“…A recent Scottish study has demonstrated comparable functional patency rates from one and two-stage procedures. 20 As with other series the complication rate and morbidity associated with minimising these complications is paramount. Interestingly, although the primary functional and secondary patency rates of BBF were comparable to BCF in our series, the primary assisted patency rate was lower.…”
Section: Utilization Of Avfmentioning
confidence: 99%